Repeated Intravenous Thrombolysis in Patients with Recurrent Ischemic Stroke in the Vertebrobasilar Territory - Černík, David; Ospalík, Dušan; Šaňák, Daniel; Cihlář, Filip (Case reports in neurology, 2021)
Acute ischemic vertebrobasilar stroke (AIVBS) is usually associated with poor outcome and prognosis and in case of basilar artery occlusion (BAO) with high mortality. Intravenous thrombolysis (IVT), as a standard recanalization therapy of acute ischemic stroke (IS) within first 4.5 h, can be administrated beyond this therapeutic time window in case of symptomatic BAO. Repeated IVT is generally contraindicated in case of early recurrent IS, despite a risk of poor outcome or death after recurrent IS. The aim was to present 2 cases of repeated IVT for recurrent AIVBS and discuss specific situations where repeated IVT may be considered. Up to now, repeated IVT has been reported only in recurrent stroke in anterior circulation.
Keywords: Eptifibatide; Basilar artery occlusion; Ischemic stroke; Repeated intravenous thrombolysis